How are consumer behavior and marketing strategy researchers incorporating the SDGs? A review and opportunities for future research. Issue 2 (May 2022) - Voola, Ranjit; Bandyopadhyay, Chinmoy; Azmat, Fara; Ray, Subhasis; Nayak, Lipsa
Increasing environmental challenges together with irresponsible consumption and production practices call for marketing research focused on sustainability. The United Nations Sustainable Development Goals (SDGs) provide a framework for marketers to operationalize sustainability and to build awareness and shape consumers' as well as businesses' views about responsible consumerism and sustainability. As the SDG framework continues to influence marketing literature and practice, it is important to take stock of how consumer and marketing strategy scholars have engaged with the SDGs since their announcement in 2015. To this end, we undertake a systematic literature review of 41 papers published in premier marketing journals that explicitly engage with the SDGs. The review identifies several gaps in the marketing literature that provide a basis for identifying future research opportunities. We argue that engaging with these research opportunities provides a transformational opportunity for marketing scholars to positively impact society.